Main Peculiarities of Good Listening and Reading Tasks: Focusing on Balancing Authenticity, Validity and Reliability (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
The following article denotes one of the significant aspects of the L2 acquisition process, highlighting the importance of selecting and designing appropriate reading and listening materials according to their validity, reliability, and authenticity.